Scavenging in the genus Natrix - Cesar Ayres (Acta Herpetologica, 2012)
Scavenging is reported as an unusual behaviour of snakes. However, it is likely more common than is supposed. Here I report the use of dead newts as prey source by water snakes of the genus Natrix at a dam in north-western Spain. Juveniles and adults viperine snakes (Natrix maura), and also an adult grass snake (Natrix natrix) were found feeding on newt carcasses.